Berpikir Kritis Siswa Kelompok Homogen dalam Pemecahan Masalah Kolaboratif Materi Lingkaran - Rachma Mufidah, Latifah Nuryah; Siswono, Tatag Yuli Eko (MATHEdunesa, 2024)
Critical and collaborative thinking are skills that need to be learned in the 21st century. One of the things that can build critical thinking is collaboration. Collaboration is a joint involvement in a coordinated effort to solve problems together through interactions that help each other and understand their tasks to achieve shared goals.The purpose of this study is to describe students' critical thinking in collaborative problem solving of circle material. The type of research used is descriptive research with a qualitative approach. The research subjects were students of SMP Negeri 25 Surabaya grade 8 who were paired with 2 people to solve the problem of circle material. Data collection was conducted in two meetings, one meeting for collaborative problem solving test and one meeting for interview.The results of data analysis show students in homogenous groups of high and high categories can achieve the critical thinking indicators such as interpretation, analysis, inference, evaluation, explanation, and self-regulation and the role of collaboration runs well. The low and low category subjects were lacking in fulfilling the indicators of analysis, inference, evaluation, explanation and self-regulation. The collaborative role of these subjects lacks interaction and there is no exchange of information.